Nonthermal Ultrafast Optical Control of Magnetization Dynamics by Linearly Polarized Light in Metallic Ferromagnet. Issue 6 (3rd January 2023) - Shi, Jingyu; Zhao, Zirui; Dai, Yu; He, Jiang; Li, Tao; Liang, En; Wang, Jun; Ni, Gang; Sheng, Chuanxiang; Wu, Di; Zhou, Shiming; Chen, Liangyao; et al.
Abstract: Coherent optical control of the magnetization in ferromagnetic (FM) mediums using ultrafast nonthermal effect paves a promising avenue to improve the speed and repetition rate of the magnetization manipulation. Whereas previously, only heat‐induced or helicity‐dependent magnetization dynamics are demonstrated in metallic ferromagnets. Here, the linearly‐polarized light control of magnetization is demonstrated in FM Co coupled with ferroelectric (FE) BiFeO3 by tuning the light polarization direction. It is revealed that in the Co/BiFeO3 heterostructure excited by femtosecond laser pulses, the magnetization precession amplitude follows a sinusoidal dependence on the laser polarization direction. This nonthermal control of coherent magnetization rotation is attributed to the optical rectification effect in the BiFeO3 layer, which yields a FE polarization depending on the light polarization, and the subsequent modulation of magnetic energy in Co by the electrostriction‐induced strain. This work demonstrates an effective route to nonthermally manipulate the ultrafast magnetization dynamics in metallic ferromagnets. Abstract : A new strategy of ultrafast nonthermal control of magnetization is adopted by coupling the metallic ferromagnet with the ferroelectric material. It utilizes the advantages of pronounced optical rectification effect and ferroelastic response in BiFeO3 . The laser irradiation on the Co/BiFeO3 heterostructure leads to a sinusoidal dependence of ultrafast magnetic torque impinged upon the magnetization precession on the light polarization direction.